2007
DOI: 10.1002/chem.200700352
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Metal‐Catalyzed Iminations of Sulfoxides and Sulfides

Abstract: A comparative study of the imination of sulfur compounds with various metal catalysts in combination with isolated or in situ generated iminoiodinanes (PhI==NR) as nitrogen sources is presented. The influence of the metal catalyst towards the imination of a variety of substituted sulfoxides has been evaluated. Moreover, the effect of the different oxidation states of sulfur on the reactivity and selectivity of the nitrogen transfer redox process in the formation of sulfilimines and sulfoximines was studied. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…The subsequent imidation was performed with PhINNs in the presence of a catalytic amount of iron(II) triflate providing fully protected methionine derivative 12cb in 87% yield. Cleavage of the nosyl group of the sulfoximine nitrogen was achieved using a mixture of thiophenol and Cs 2 CO 3 28. In this manner, compound 14c with an NH‐sulfoximidoyl moiety was obtained in 74% yield.…”
Section: Methodsmentioning
confidence: 99%
“…The subsequent imidation was performed with PhINNs in the presence of a catalytic amount of iron(II) triflate providing fully protected methionine derivative 12cb in 87% yield. Cleavage of the nosyl group of the sulfoximine nitrogen was achieved using a mixture of thiophenol and Cs 2 CO 3 28. In this manner, compound 14c with an NH‐sulfoximidoyl moiety was obtained in 74% yield.…”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, cobalt‐catalyzed nitrene transfer to sulfur atoms remains largely unexplored. While a single example of [Co(ClO 4 ) 2 ]‐catalyzed sulfoximidation of methyl phenyl sulfoxide with (in situ formed) PhINNs has been reported, [15] there are no reported examples of cobalt‐catalyzed sulfimidation of sulfides, to the best of our knowledge. Given recent developments in cobalt‐catalyzed N ‐group transfer reactions, [16–18] we decided to investigate cobalt‐catalyzed sulfimidation via nitrene transfer to sulfides focusing on chemoselective transformations in the presence of other nitrene‐accepting functional groups (alkenes and weak C−H bonds).…”
Section: Introductionmentioning
confidence: 95%
“…Ligand 1a was successfully employed in an enantioselective Agcatalyzed amination of CÀHb onds which was assumed to occur by an enantioselective nitrene insertion [14] at the hydrogen-bonded substrate.A lthough silver catalysis has been shown to be av iable approach for the amination [15,16] and aziridination [15,17] of organic substrates it has not been extensively applied to sulfides.B olm and co-workers found that silver nitrate acts in combination with an achiral terpyridine ligand as ac atalyst to mediate the imidation of sulfoxides to generate sulfoximines. [18,19] Tw osulfimides were obtained in high yields (77 %a nd 83 %) albeit in racemic form.…”
Section: Resultsmentioning
confidence: 99%